The Darkest Page in the History of Lithuanian Journalism: anti-Semitism in Legal Press During the Second Half of 1941 - Bražiūnas, Mantas (Žurnalistikos tyrimai, 2017)
There is a saying of warfare: inter arma silent musae – when arms speak, muses are silent. And yet some Lithuanian journalists had found their inspiration even in 1941 – when Lithuania was at the epicenter of war and the Holocaust. Later on, this period will be defined as the darkest page in the history of Lithuanian journalism,1 because the genocide of the Jews had been accompanied by an outbreak (on a scale previously unseen) of anti-Semitism in Lithuanian press. It is a well-known but little-studied case. Moreover, usually anti-Semitism within the press was interpreted only as an integral part of the Nazi propaganda in Lithuania. It is not surprising, since this already mythical concept appears as a “phantom,” most often when someone wishes to employ easily understandable arguments for justification or explanation. Political activists sought to restore the independence of Lithuania in the summer of 1941. It was the main reason why they also rebuilt press organizations in the country. Initially, it was certainly not a Nazi propaganda project. Therefore, the same Lithuanian activists could be held responsible for the escalation of hate aimed at Jews as much as the Germans. On the other hand, Lithuanian anti-Semitism can be seen in many ways: as a form of revenge, a collaboration strategy or an uncritical adoption of totalitarian Nazi rhetoric, finally, as an integral part of Lithuanian nationalism or National Socialism – a pragmatic ideology used to achieve political goals. So, this essay revolves around two main questions: who and why published the anti-Semitic writings within Lithuanian press in 1941? Study findings are based on a combination of primary sources and secondary literature. This study was also supplemented by an analysis of hundreds of anti- Semitic articles (their headlines and content) published June 24-December 31, 1941. The purpose of this analysis is to characterize the discourse of anti-Semitism in Lithuanian press. Our study seeks to identify the authors of these publications and their sources, determine the most common topics and genres, as well as to see whether there was a proposition (direct or indirect) to prosecute and use physical violence or even murder Jewish individuals.
Keywords: journalism; press; anti-Semitism; the Holocaust; Lithuania